Synthetic spirocyclic endoperoxides: new antimalarial scaffolds. Issue 2 (25th November 2014) - Brindisi, Margherita; Gemma, Sandra; Kunjir, Sanil; Di Cerbo, Luisa; Brogi, Simone; Parapini, Silvia; D'Alessandro, Sarah; Taramelli, Donatella; Habluetzel, Annette; Tapanelli, Sofia; Lamponi, Stefania; Novellino, Ettore; et al.
Abstract : Design, synthesis and molecular docking calculation studies led to the identification of novel spirocyclic peroxides with in vitro and in vivo antimalarial activity. Abstract : Here we report the development of a straightforward synthetic procedure for the preparation of spirocyclic endoperoxides as synthetic analogues of the natural product dihydroplakortin. The peroxides presented here are more potent antiplasmodials than dihydroplakortin itself and we proved for the first time their antimalarial activity in vivo .